Optimization of treatment methods for chronic diseases of the nose and paranasal sinuses combined with chronic dacryocystitis - N.J. Khushvakova; F.A. Nurmukhammedov; U.F.Davronov (Proceedings of The ICECRS, 2019)
The pathogenesis of the overgrowth of dacryorrhinostoma is based on many factors from the development of granulations and scars in the area of ​​the bone opening to the development of the commissural opening, mucositis in the nasal cavity to purulent persistent forms of rhinosinusitis in the area nose-lacrimal duct. To improve the reparative processes after the operation of endoscopic dacriocystomy with the installation of silicone stent-drainage (from the intubation tube), a zinc hyalrate solution was used.